Blood lead level among children aged 06-36 month in Kathmandu valley, Nepal 2015. (2016)
SUMMARY: Introduction: Lead is a highly toxic metal which has contaminated our environment and creates health problems. Even a very small intake of lead is a serious and sometimes creates a fatal condition. Young children are at the greatest risk of health problems related to lead exposure. This study aims to assess blood lead levels (BLLs) among the children 06-36 months residing in Kathmandu Valley, Nepal. Materials and methods: This was a hospital based cross -sectional study. A total of 312 children of 06-36 months old visiting paediatric unit of the TUTH, Patan Hospital and Siddhi Memorial Hospital of Kathmandu valley were enrolled in the study. Anodic Stripping Voltammetry (ASV) portable instrument was used to determine the blood lead level in children.Written informed consent were taken from parents and required data were collected using the structured questionnaire from the parents. Data were analyzed using the SPSS version 16. Results: Out of the total 312 children enrolled in the study, 64.4% had the BLL exceeding the cut off points of centers for diseases control and prevention (CDC), (≥5µg/dl), while 35.6% had less than 5µg/dl of BLLs. A significant association was found between BLLs and the enamel paints painted in different parts of the house like walls, windows and doors (p=0.001). Further, multivariate analysis showed that BLLs was 4.5 times higher in children playing with dirt and dust (p=0.006) and children belonging to the ethnic group such as Dalits, disadvantaged Janajatis and Non-Dalits Terai caste groups, religious minorities and relatively advantaged janajatis had found significantly higher BLL compared to upper caste group(p=0.02). Conclusion: This study demonstrates that children living in homes with the enamel paints on walls, windows and doors, belonging to the lower ethnic group and playing with dirt and dust had found significantly higher BLL. The evidence indicates that lead exposure must be addressed appropriately by health policy makers and argues for an improvement of natural home environment i.e. to reduce the burden of lead in paints. Society and parents need to be aware of the problem on lead poisoning during their childhood. Keywords: Lead exposure, poisoning, blood lead level, Nepal